2018
DOI: 10.1016/j.jhsa.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Driving Cost Variation for Distal Radius Fracture Open Reduction Internal Fixation

Abstract: This study identifies modifiable factors that may lead to cost reduction for distal radius ORIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…VDO costing methods have been previously described, which allow access to total direct costs for materials used for patient care, facility utilization direct costs (including sterile processing costs), and timebased cost allocations including procedure/operative time and cost of staff involved in care (nursing, surgical technicians, and medical assistants). 1,13,14,16,20,23 As the outcome measure was total direct costs, rather than payments, reimbursement for the surgeon, anesthesiologist, and facility were not included; however, time-allocated costs for the surgeon, anesthesiologist, and facility use were captured by the database. All cost categories captured by the VDO tool are further illustrated in ►Appendix A.…”
Section: Operating Room Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…VDO costing methods have been previously described, which allow access to total direct costs for materials used for patient care, facility utilization direct costs (including sterile processing costs), and timebased cost allocations including procedure/operative time and cost of staff involved in care (nursing, surgical technicians, and medical assistants). 1,13,14,16,20,23 As the outcome measure was total direct costs, rather than payments, reimbursement for the surgeon, anesthesiologist, and facility were not included; however, time-allocated costs for the surgeon, anesthesiologist, and facility use were captured by the database. All cost categories captured by the VDO tool are further illustrated in ►Appendix A.…”
Section: Operating Room Protocolmentioning
confidence: 99%
“…This has successfully identified areas of high variability in cost, leading to improved value of care delivered 1 and identification of sources of cost variation that may be targeted to improve value. [13][14][15][16][17][18] In the current study, the VDO tool was utilized to answer our primary study question of whether the choice of surgical setting (OR vs. PR), and anesthetic type (local only, BB, MAC, or GA) affect surgical encounter costs for DQR.…”
mentioning
confidence: 99%
“…Although we did not have enough variation in implant manufacturer at our institution to evaluate the contribution of this variable to cost variation, prior studies have shown that manufacturer significantly influences cost variation. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Previous literature using this tool in orthopedics has demonstrated that pharmacy, laboratory, and imaging costs comprise a relatively small portion (<5%) of the SETDC and therefore contribute minimally to surgical cost variation. 19 , 20 , 22 Therefore, we chose to omit these categories rather than exclude all inpatient surgeries. Additionally, professional payments including those to the surgeon and anesthesiologist, and indirect costs such as facility or equipment depreciation, are not included.…”
Section: Methodsmentioning
confidence: 99%
“…30 Furthermore, due to differences in contracting between different hospitals, implant costs are known to vary widely across the nation. [31][32][33] If bundled payments for hip fractures are implemented on a national scale, controlling the cost variation of these implants will be one of the few ways to bring about value in care. Implementing value-based purchasing programs that ensure alignment of physician incentives with that of the hospital involves careful review of potential conflicts of interest between the implant companies and physicians, uses price transparency to compare implant costs across other institutions, and involves a technology review of the efficacy of new implants will be an effective way of implementing an aggressive contracting policy with industry companies to reduce costs.…”
Section: Challenges and Opportunities Of Including Hip Fractures In Bmentioning
confidence: 99%